The Effects of Mechanical and Thermal Loads during Lithium‐Ion Pouch Cell Formation and Their Impacts on Process Time. Issue 2 (10th May 2019) - Heimes, Heiner Hans; Offermanns, Christian; Mohsseni, Ahmad; Laufen, Hendrik; Westerhoff, Uwe; Hoffmann, Louisa; Niehoff, Philip; Kurrat, Michael; Winter, Martin; Kampker, Achim
Abstract : The most cost‐intensive components of the battery system for electric vehicles are the lithium‐ion battery cells. Thus, to reduce the overall cost of a battery system, a clear objective is to reduce the production cost of lithium‐ion battery cells. Cost drivers are to be identified, which are essential to enable potentials for cost reduction. In particular, the formation and aging process represents a high potential for process cost reduction because of its enormous process time expenditure. The automotive industry requires up to 3 weeks for the formation and aging process of a single lithium‐ion battery cell. Due to the high relevance of these processes, the research project OptiZellForm as part of the ProZell Cluster examines those production steps in detail. Environmental conditions such as mechanical load and elevated temperature as well as the electrical and chemical properties influencing the formation and aging process are investigated. The focus of this study is the investigation of the mechanical exertion and elevated temperature with regard to the reduction of the formation process duration and thus the reduction of the production cost. For this reason, a specially designed device is used to investigate these parameters for lithium‐ion battery cells. Abstract : Cost drivers in lithium‐ion battery cell production are essential to enable potentials for cost reduction. In particular, the formation and aging processes represent a high potential for cost reduction because of the enormous time expenditure. Environmental conditions such as mechanical load and temperature as well as the electrical and chemical conditions during formation and aging are investigated.